Program unit 6 - self-management - Veiga-Branco, Augusta (2019)
Emotional regulation or Emotion Self-regulation or Emotions management – involves controlling or redirecting one's disruptive emotions and impulses and adapting to changing circumstances. Emotional relaxation - a state of deep rest that is the polar opposite of the stress response. The relaxation response puts the brakes on stress and brings body and mind back into a state of equilibrium. Flow - a positive state of the body during activities. During flow, people typically experience deep enjoyment, creativity, and a total involvement with life. Mihaly Csikszentmihalyi‘s famous investigations of "optimal experience" revealed that what makes an experience genuinely satisfying is a state of consciousness called flow.